WHAT IS THE VALUE OF REFLECTION FOR TEACHERS? A STUDY ON PRIMARY SCHOOL TEACHERS - Miruna Luana MIULESCU; Antoaneta-Firuţa TACEA (National Centre for Policy and Evaluation in Education, 2023)
The concept of reflective teacher has been studied extensively in the last three decades and has facilitated the shift in the teacher education orbit from attainment to development. Our study seeks to discover the value of reflection for teachers and in what way their practices could potentially be influenced by it. The participants of the present study were 11 primary school teachers from Bucharest, Romania. By making use of a phenomenological qualitative inquiry approach, data were collected through a focus group and a reflective journal. The key findings indicate that the participants in the study are willing to embrace an investigative attitude that will help improve and assess practice, even if they are not used to it and do not always have the proper time to analyze their teaching practices daily. Moreover, multiple advantages of keeping a reflective journal were recognized: facilitation of teaching, enhancement of innovation, impact on professional growth, enhancement of problem-solving skills, improvement of overall effectiveness, and promotion of a positive learning environment.